2011
DOI: 10.1159/000324714
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal versus Sub-Tenon Posterior Triamcinolone Injection in Bilateral Diffuse Diabetic Macular Edema

Abstract: Purpose: To compare the efficacy of intravitreal and sub-Tenon (ST) posterior triamcinolone injection in the treatment of bilateral diabetic diffuse macular edema (DDME). Methods: 28 eyes of 14 diabetic patients with bilateral DDME were included in this prospective randomized study. One eye of each individual received a sub-Tenon (ST) posterior triamcinolone injection (ST group), whereas the fellow eye received an intravitreal triamcinolone injection (IV group). All eyes were treated with supplementary focal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
0
17
0
3
Order By: Relevance
“…Peribulbar or subtenon's steroid injections have been used to treat diabetic macular edema either as monotherapy or as adjunctive therapy to laser [16,17,24,28] . Although they are not considered ideal to obtain a therapeutic dose of cortisone at the level of the retina [29,30] , short-term efficacy has been demonstrated with transient improvement to both retinal thickness and visual acuity but less effective than intravitreal therapy [16,17,30] .…”
Section: Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peribulbar or subtenon's steroid injections have been used to treat diabetic macular edema either as monotherapy or as adjunctive therapy to laser [16,17,24,28] . Although they are not considered ideal to obtain a therapeutic dose of cortisone at the level of the retina [29,30] , short-term efficacy has been demonstrated with transient improvement to both retinal thickness and visual acuity but less effective than intravitreal therapy [16,17,30] .…”
Section: Injectionsmentioning
confidence: 99%
“…Other complications reported are blepharoptosis, orbital fat atrophy, strabismus and conjunctival necrosis [31,32] . It is important to add, that intra-ocular pressure (IOP) is not increased by the use of the posterior sub-Tenon's approach in comparison to anterior sub-Tenon or intravitreal triamcinolone acetonide (IVTA) injections with the exception of steroid responder patients, the risk of IOP elevation is 44% steroid responders compared to 13% in non steroid responders [28,[31][32][33][34] .…”
Section: Injectionsmentioning
confidence: 99%
“…This study only included patients with good visual acuity; so PSTI of triamcinolone may still be a useful adjunct for diffuse diabetic macular edema with poor visual acuity when performed prior to grid focal laser, as has been suggested by other studies [42,43]. The duration of effect has been found to be longer following IVTA compared to PSTI [44,45]. A few studies have found that PSTI of triamcinolone are associated with an increase in IOP but the degree of IOP increase to be lower than IVTA [46,47].…”
Section: Periocular Versus Intravitreal Injectionsmentioning
confidence: 80%
“…Transscleral permeation may be a viable alternative because of its large and accessible surface area, high degree of water content rendering it conductive to hydrophilic molecules, hypocellularity with an attendant paucity of proteolytic enzymes and protein-binding sites, and permeability that does not appreciably decline with age (Olsen et al 1995(Olsen et al , 1998Edwards Diffusion of macromolecules through sclera & Prausnitz 1998). Several clinical studies even have proved the effect of subtenon injection of triamcinolone acetonide for uveitic cystoid macular oedema and diffuse diabetic macular oedema (Bae et al 2011;Yalcinbayir et al 2011).…”
Section: Introductionmentioning
confidence: 99%